2021
DOI: 10.14412/1996-7012-2021-6-61-66
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of leptin in systemic lupus erythematosus

Abstract: Objective: to study the frequency of hyperleptinemia in patients with systemic lupus erythematosus (SLE), its relationship with clinical and laboratory manifestations of the disease, drug therapy, and other metabolic disorders.Patients and methods. The cross-sectional study included 46 women with a definite diagnosis of SLE (median age 40 [31; 48] years) and disease duration 3.0 [0.9; 9.0] years. Glucocorticoids (GC) were received by 38 (83%) patients, hydroxychloroquine – by 35 (76%), immunosuppressants – by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…We found that most of the studies showed that SLE patients had higher leptin levels in plasma or serum in comparison to healthy controls. In a cross-sectional study that included only SLE patients, Kondratyeva et al reported that 76% of the patients had hyperleptinemia [22]. In contrast to these findings, in a study performed on an Indonesian population, the SLE group had a higher mean leptin level, but the difference was not statistically significant [19].…”
Section: Leptin Levels In Patients With Slementioning
confidence: 92%
See 1 more Smart Citation
“…We found that most of the studies showed that SLE patients had higher leptin levels in plasma or serum in comparison to healthy controls. In a cross-sectional study that included only SLE patients, Kondratyeva et al reported that 76% of the patients had hyperleptinemia [22]. In contrast to these findings, in a study performed on an Indonesian population, the SLE group had a higher mean leptin level, but the difference was not statistically significant [19].…”
Section: Leptin Levels In Patients With Slementioning
confidence: 92%
“…Of the 12 studies included in the review, only 10 had information regarding the relationship between leptin levels and disease activity measured by SLEDAI. Out of these, only three studies showed a positive correlation between disease activity measured by SLEDAI and leptin level [17,21,22]. In 2020, Yuan et al…”
Section: Disease Activity and Leptinmentioning
confidence: 99%